Penerapan Good Corporate Governance pada Badan Usaha Milik Desa di Provinsi Jawa Barat - Agni Grandita Permata Sari (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
Village-Owned Enterprise (BUMDes) is an important component to improve the village economy. The number of stimulus programs that have been delivered by the government has not been able to make BUMDes in West Java into the category of ‘advanced’ and ‘large’. The majority of BUMDes in West Java are in the category of ‘pioneer’ and there are only a few BUMDes that are in the ‘growing’ category. For the ‘mature’ category, there is only one BUMDes, namely Niagara BUMDes in Wangisaraga Village, Majalaya District in Bandung Regency. The purpose of this study is to see the implementation of the principles of Good Corporate Governance (GCG) in managing BUMDes in West Java Province. This research was conducted on three BUMDes spread over three regencies/cities in West Java Province, namely Bandung Regency, West Bandung Regency and Banjar City which represent BUMDes in the category of pioneering, growing and mature. The analysis is conducted using the concept of GCG. This study uses a qualitative method with an inductive approach. This study shows that the implementation of GCG includes the principles of transparency, accountability, responsibility, independence, and fairness is still weak. In the first principle, transparency is only fulfilled by the existence of financial reports, meanwhile BUMDes does not have standards and targets for financial dan performance reports. Then, in the second principle, accountability is only limited to determining the details of the duties and responsibilities of its structures and does not yet have and implement other indicators. Furthermore, in the third principle, the responsibility of BUMDes has not been seen from the fulfillment of social responsibilities in accordance with what is mandated in the AD/ART BUMDes. Meanwhile, in the fourth principle, independence does not work with the discovery of several forms of village head intervention, namely in the placement of employees. Finally, in the fifth principle, it was found that the implementation of the principle of Fairness to each BUMDes was quite good, marked by the inclusiveness of decision making. However, what is noted is the employee recruitment process which still contains elements of nepotism from the village head.